Electric field tuning of phase separation in manganite thin films - Lourembam, James (2014)
In this paper, we investigate the electric field effect on epitaxial Pr0.65(Ca0.75Sr0.25)0.35MnO3 thin films in electric double-layer transistors. Different from the conventional transistors with semiconducting channels, the sub(micrometer)-scale phase separation in the manganite channels is expected to result in inhomogeneous distribution of mobile carriers and local enhancement of electric field. The field effect is much larger in the low-temperature phase separation region compared to that in the high-temperature polaron transport region. Further enhancement of electroresistance is achieved by applying a magnetic field, and a 250% modulation of resistance is observed at 80 K, equivalent to an increase of the ferromagnetic metallic phase fraction by 0.51%, as estimated by the general effective medium model. Our results illustrate the complementary nature of electric and magnetic field effects in phase-separated manganites, providing insights on such novel electronic devices based on complex oxides.